2017
DOI: 10.1371/journal.pone.0171627
|View full text |Cite
|
Sign up to set email alerts
|

Optimal and safe standard doses of midazolam and propofol to achieve patient and doctor satisfaction with dental treatment: A prospective cohort study

Abstract: BackgroundThe incidences of morbidity and mortality caused by pharmacosedation for dental treatment have not yet reached zero. Adverse events are related to inappropriate respiratory management, mostly originating from an overdose of sedatives. Since sedation is utilized for the satisfaction of both the dentist and the patient, the optimal dose should be minimized to prevent adverse events. We attempted to define the optimal doses of midazolam and propofol required to achieve high levels of patient and dentist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
2
15
0
1
Order By: Relevance
“…According to our results, it can be assumed that sex is not a determining factor that expresses the need for pharmacological sedation. The mean age in the studies of Jerath et al and Masuda et al were close, with the first one being 40, with a minimum age of 20 years and a maximum of 85, and the second study being 47 years, varying from 9 to 85 years old (14,19). When compared to the mean of our study (18 years), it can be observed that the means were higher; however, variations of ages were close to the present study, which presented ages from 6 to 78 years.…”
Section: Discussionmentioning
confidence: 78%
“…According to our results, it can be assumed that sex is not a determining factor that expresses the need for pharmacological sedation. The mean age in the studies of Jerath et al and Masuda et al were close, with the first one being 40, with a minimum age of 20 years and a maximum of 85, and the second study being 47 years, varying from 9 to 85 years old (14,19). When compared to the mean of our study (18 years), it can be observed that the means were higher; however, variations of ages were close to the present study, which presented ages from 6 to 78 years.…”
Section: Discussionmentioning
confidence: 78%
“…Dental anxiety is a common aspect of oral-surgical procedures, and patients may benefit from the use of conscious sedation [10]. The advantages of conscious sedation may include lower patient anxiety [8,19,21,23,25], reduced post-surgical pain [27] increased patient and surgeon satisfaction [28], and inhibition of gag reflex [29]. In addition, it can be safely delivered in a non-operating room environment [30] and to patients with challenging behaviors as an alternative to general anesthesia [5].…”
Section: Discussionmentioning
confidence: 99%
“…Для пацієнта має значення якість медикаментозного сну, ступінь задоволення та зручність на всіх етапах лікування. Наприклад, психологічний комфорт при спілкуванні з медичним персоналом перед процедурою; застосування заспокійливих лікарських засобів премедикації для зменшення тривоги та страху; відсутність болісних подразників, епізодів відновлення свідомості, галюцинацій під час лікування та різноманітних ускладнень після нього, таких як біль, нудота, подовжене пробудження або безсоння; адекватне знеболення, можливість вести звичний спосіб життя в післяопераційному періоді [16,17]. Сучасні дослідження доводять високий ступінь ефективності при застосуванні різноманітних методик седації [18,19].…”
Section: ефективність та безпечність амбулаторної седаціїunclassified